Visible and Near‐Infrared Imaging with Nonfullerene‐Based Photodetectors. Issue 7 (11th June 2018) - Gasparini, Nicola; Gregori, Alberto; Salvador, Michael; Biele, Markus; Wadsworth, Andrew; Tedde, Sandro; Baran, Derya; McCulloch, Iain; Brabec, Christoph J.
Abstract: The solution‐processed organic photodetectors underpin an emerging technology with inherent implications in the biological sensors and imaging displays. Conventional organic photodiodes, the core element of an organic photodetector, rely mainly on fullerene‐based acceptors, which in combination with high and middle bandgap donors, limit the spectral photosensitivity to the visible range. Even in the case of low bandgap polymers the oscillator strength and thus the extinction coefficient are usually limited in the NIR due to the nature of molecular orbital hybridization. Instead, it is showed that pairing prototypical poly(3‐hexylthiophene) (P3HT) with rhodanine‐benzothiadiazole‐coupled indacenodithiophene (IDTBR), a nonfullerene electron acceptor absorbing beyond 750 nm, as the photoactive material of a simple photodiode results in a highly efficient organic photodetector with a record responsivity of 0.42 A W −1 and external quantum efficiency (EQE) of 69% in the NIR (755 nm). Nonfullerene‐based photodiodes are processed on amorphous silicon active matrix backplanes to realize large area flat panel photodetector imagers able to detect objects under visible and NIR light conditions with an exceptional combination of responsivity, dynamic response and image crosstalk. Abstract : Organic photodetectors (OPD) based on nonfullerene acceptor (IDTBR) are reported that feature low dark current ( J d = 30 nA cm −2 ) and high responsivity of 0.42 A W −1 . Moreover, flat panel imagers able to detect objects under visible and near‐infrared light conditions are realized, opening a bright future for full color detection and image sensing.